Prevalence, incidence and risk factors for acquisition and colonization of extended-spectrum beta-lactamase- and carbapenemase-producing Enterobacteriaceae from dogs attended at a veterinary hospital in Spain - Ortiz Díez, Gustavo; Luque Mengíbar, Ruth; Turrientes López, María Carmen; Baquero Artigao, María Rosario; López Gallifa, Raúl; Maroto Tello, Alba; Fernández Pérez, Cristina; Ayllón Santiago, Tania (My University, 2023)
The last 10 years have seen a progressive increase in antibiotic resistance rates in bacteria isolated from com panion animals. Exposure of individuals to resistant bacteria from companion animals, such as extendedspectrum beta-lactamase- (ESBL) and carbapenemase- (CPE) producing Enterobacteriaceae, can be propitiated. Few studies evaluate the incidence and risk factors associated with colonization by multidrug-resistant bacteria in dogs. This work aims to estimate the prevalence, incidence and risk factors associated with colonization of ESBL-E and CPE-E in 44 canine patients hospitalized in a veterinary hospital. The antimicrobial susceptibility of Enterobacteriaceae strains was analyzed and the molecular detection of resistant genes was performed. A prevalence of 25.0% and an incidence of ESBL-E of 45.5% were observed in dogs colonized by Enterobac teriaceae at hospital admission and release, respectively. Escherichia coli, Klebsiella pneumoniae, Citrobacter koseri and Morganella morganii were identified as ESBL-producing bacterial species. Resistance genes were detected for ESBL-producing strains. No CPE isolates were obtained on the CPE-selective medium. The administration of corticosteroids prior to hospitalization and the presence of concomitant diseases were associated with coloni zation by these bacteria in dogs. Considering that one-quarter of the patients evaluated were colonized by ESBL-E, companion animals should be considered as potential transmission vehicles and ESBL-E reservoirs for humans. Special care should be taken in animals attended at veterinary hospitals, as the length of stay in the hospital could increase the risks.